Soil applied cobalt alters the growth parameters and dry matters production of Bhendi (Abelmoschus esculentus L.) - Kaliyamoorthy Jayakumar; P. Aksah (Innovations in Agriculture, 2022)
In this study, an economically important crop plant Bhendi (Abelmoschus esculentus L.) were treated with various concentrations of cobalt to test its effect on the growth of the plants. For the growth of many plants, cobalt is necessary. Conversely, higher amounts of cobalt are poisonous to plants. Seeds were cultivated in pots with soil that had not been treated (the control) and soil that had cobalt added to it in doses of 50, 100, 150, 200, and 250 mg kg-1. For each sample, the several morphological characteristics including root length, shoot length, number of nodules, total leaf area, dry weight of root and shoot per plant, and leaf area were measured. Soil cobalt level of 50 mg kg-1 was found beneficial to the plants.